Political rights and their guarantees under the constitution of the Republic of Iraq 2005 (analytical study) - Radhi, Shamim; Abdullah, Adel (Journal of Legal Sciences, 2022)
It guarantees the political rights of individuals to participate in public affairs and political life, but these rights require their protection by the existence of guarantees that guarantee the protection of these rights and ensure that they are actually exercised by individuals. The Constitution of the Republic of Iraq for the year 2005 We dealt with the type of protection granted to these rights, as well as the statement of the types of political rights and the position of the Constitution of the Republic of Iraq for the year 2005 towards them.